AN 8-WEEK HIGH-INTENSITY INTERVAL TRAINING PROGRAM’S IMPACT ON FEMALE ATHLETES’ VITAL CAPACITY - Deka, Rupshikha; Kumar, Ajay; Singh, Dr. Amarpreet (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The experimental study was conducted to evaluate the effect of 8 weeks of high-intensity interval training vital capacity of female athletes. The present study was conducted on sixteen (n=16) female athletes from Punjabi University, Patiala. All subjects ranged aged 18-26 were selected in terms of purposive samples under the sampling method of non-probability sampling. The required data were collected through the administration of standardized instruments for the measurement of selected variables. Pre-Test data was collected to measure the primary status of vital capacity before subjects underwent 8 weeks of planned training intervention. Post-Test data was collected after training intervention to evaluate the effect of high-intensity interval training on the vital capacity of female athletes. For analysis and interpretation of data statistical tools were applied e.g., Paired ‘t’, to find out the difference, and compare mean, standard deviation and standard error mean. The result shows that 8 weeks of high-intensity interval training remarkably increase vital capacity in female athletes.